PENGARUH E-SATISFACTION ON RE-USE INTENTION PADA PLATFORM BCA MOBILE BANKING - Irene Ariska Limanua; Aldi Pamungkas; Abdul Yusuf (Universitas Boyolali, 2022)
In this modern era, all activities are based on technology. One of them is the economic sector, all economies are starting to switch to using advanced technology such as e-banking. And one of the determinants of the company's success to increase the re-use intention of mobile banking applications is the high level of user satisfaction. This study uses a quantitative approach by spreading questionnaires and measurements are carried out using the Likert scale. This research was conducted on the BCA Mobile Banking platform, where the population in this study is all BCA Mobile Banking users. Purposive sampling techniques were used in determining the number of study samples totaling 102 people, and the data was analyzed using SPSS software with simple linear regression analysis. The results showed that e-satisfaction had a positive and significant effect on reuse intentions